Prediction of Temperature Gradient and Soil Water Content through a Sandy Clayey Soil by TEMP/W Simulations - Arshad, Imran; Babar, Muhammed Muneer; Javed, Natasha (PSM Biological Research, 2017)
In the present research work the combined effect of temperature gradient and water-content on soil water movement through the sandy clayey soil has been computed by using the slave program of Geo-Slope software i.e. SEEP/W and TEMP/W respectively. The 2-D mesh was developed using TEMP/W which was 25 m long and 14 m in depth and having 390 nodes and 350 elements respectively. The soil region was assumed to be a sandy clayey soil with bulk density 1.55 gm/cm3 and saturated hydraulic conductivity (Ks) (1.77 x 10-6 m/s) accordingly. The initial atmospheric and soil temperature was kept at 45Â°C and 20Â°C respectively. The irrigation of 1 inch water was applied on the surface of the land and the time step sequence consists of 35 steps. The simulation results revealed that after infiltration process the temperature at the soil surface started rising due to low water content the volumetric heat capacity of soil became smaller and therefore maximum heat rose. While at all other depths there was an abrupt increase in temperature for the first 5 days. However, after 15 to 20 days temperature became somewhat constant at depth 30 inch till depth 48 inch. Furthermore, at 6 inch depth, a sharp transition was occurred from 1st day to 15th day in which water content decreased from 0.286 m3 water / m3 to 0.261 m3 water / m3 because of pore space available for air intrusion resulting in higher evaporation potential. After 20th day the water content at 6 inch depth was found unchanged for the rest of the period. However, due to higher evaporation from the open water surface and downward temperature gradient, at soil depths i.e. 12, 18, and 24 inches the water content decreased gradually and became constant after 20 to 25 days. For the remaining soil depths the water content remained at the equilibrium state.